Peuplement Spontané Et Accès À L’éducation Primaire Dans La Commune De Bantè Au Centre Du Bénin - Akobi K.; Yabi Ibouraima; Agnon Nacisse; Amoussou Ernest; Boko Michel (European Scientific Journal, ESJ, 2017)
Achieving universal primary education is the second Millennium Development Goals that Benin missed in 2015 with a national rate of 74 percent. The reasons for this failure are varied with notable spatial specificities. The present research aims to contribute to the analysis of the specific causes of this failure in the Bantè Commune. The data used relate to the number of children enrolled in schools, the number of schools, and the number of settlements (villages, hamlets, and manned farms) on several dates in the Commune. In addition, information was collected from selected households in several localities. Individual interviews and groups as well as direct field observations were the collection techniques used. The tools and parameters of the descriptive statistics and the cartographic approach made it possible to process the data collected. The results show a disparity in the spatial distribution of primary schools compared to inhabited places. The result shows a geographical inaccessibility of schools for the children of many hamlets and farms. This situation is mainly inherent to a spontaneous settlement dynamics which characterizes the Commune. This concern, therefore, deserves consideration if access to primary education is a global challenge that is again relaunched by 2030. This is usually done within the framework of the Sustainable Development Goals.